The properties of Cu films deposited by high rate magnetron sputtering from a liquid target. (November 2019) - Bleykher, G.A.; Yuryeva, A.V.; Shabunin, A.S.; Sidelev, D.V.; Grudinin, V.A.; Yuryev, Yu.N.
Abstract: The focus of the paper is Cu films obtained by magnetron sputtering a liquid target at an average power density not exceeding 45 W/cm 2 . The deposition rates reached 140 nm/s. In the film formation, the pulsed power supplies of two types have been used. The discharge has functioned in an Ar atmosphere and in self-sustained mode. Structural and electrically conductive properties of the films have been analyzed. A comparison was made with those deposited by sputtering a cooled target with similar power. It has revealed that the evaporation of the magnetron target plays a dominant role in the formation of the structural and conductive properties of Cu films. The Cu films deposited by sputtering evaporative liquid targets have a lower electrical resistance than the films of similar thickness obtained by sputtering cooled targets. The mode of self-sustained sputtering does not significantly affect the structural properties of the films as compared with sputtering in the Ar atmosphere, but the electrical resistivity is approximately 20% lower. Due to high deposition rate in the case with evaporative targets the heating of the substrate when producing films of equal thickness turns out to be less than when using a magnetron with a cooled target. Highlights: Cu films have been obtained with 140 nm/s rate at target power density of 45 W/cm 2 . Target evaporation is dominant factor in the formation of Cu films structure. Cu films deposited using evaporating magnetron target have a lower electrical resistivity than by sputtering a cooled one. Electrical resistance of Cu films formed in the self-sustained mode is 20% lower. Substrate heating can be less in the case of evaporating magnetron target.